A escrita clownesca de Clarice Lispector: contestações do fazer literário - Sousa, Francisca Liciany Rodrigues de (2019)
The final production of Clarice Lispector's writing, namely the one that emerged after 1973, presents a greater dedication to reflect the issues of writing, literature and language. According to literary criticism, such a characteristic would be in agreement with the current artistic moment, Postmodernism. However, this fact is more eloquent than it may seem at first glance. In more than a decade dedicated to research the work of the author, we‟ve realized an interesting behavior in relation to the voice that is heard in its texts. While we dedicated to the study, in previous stages, to analyze the tragicity present in the characters, it was possible to perceive that there is a comic tone in her writing, a voice that challenges and laughs at the whole process of writing and literature. A voice that laughs at itself. We aim with this research to verify the final production of Clarice Lispector, especially in what concerns this comic posture, to which we associate the figure of a clown, a character who produces laughter and melancholy by living on the tightrope of life and staging. For this, the present research built in from a bibliographic analysis is divided into three stages. In the first one, from authors such as Giorgio Agamben (2007) and Michel Foucault (2007), we perform a history of the period called postmodern, in order to explore the contending character existing in its root and thus, later, compare with that present in the Clarice Lispector‟s work, contextualizing its period of production. For better execution, we delimit in three particular contestations: the language, the relation between real and fictional and the values of the literary work. In a second moment, we explored the figure of the clown, its constitution and its history, to personify this humorous and answering spirit of the scriptural voice of Lispector. For this, we take as base the researches of George Minois (2003), Jaques Lecoq (2003), among others. Finally, we analyze the final Lispector production, focusing on two of the author's short stories: Onde estiveste de noite (1974), Via crucis do corpo (1974). In this stage, we analyze the clownish posture present in the texts and relate other critical studies on Clarice Lispector‟s writing, such as some works by Vilma Arêas (1991,2005) and Nilze Maria de A. Reguera (2006). We believe that the new perspective brought to the analysis of the contestations and literary questions present in the final production of Lispector leads to a greater understanding of the author's poetics and, in addition, clarifies questions (such as the clownish) in works still little explored by critics.